Transcultural validation of the “Teacher Stress Inventory” (TSI) in Arabic: an exploratory study on stress among Tunisian teachers - Sai, Badyi; Mohamed, Baaziz; Dergaa, Ismail; Ceylan, Halil İbrahim; Guelmemi, Noomen; Stefanica, Valentina; Jaraya, Mohamed; Raul-Ioan, Muntean; Ben Abderrahman, Abderraouf (Frontiers in Education, 2025)
BackgroundThe Teacher Stress Inventory (TSI) is an instrument for assessing the multifaceted stressors experienced by educators. However, its original English format necessitates cultural adaptation to ensure relevance for Arabic-speaking contexts.AimThis study aimed to validate the TSI in Arabic for Tunisian teachers, assessing its psychometric properties, including factorial structure, internal reliability, construct validity, and sensitivity.MethodsWe used back-translation to validate the Arabic version of the Teacher Stress Inventory (TSI-A). We collected data from a total of 1,292 teachers aged 45.22 ± 5.99 years. These participants from primary and secondary schools across Tunisia formed an exploratory sample of 544 teachers (52.60% female) to determine the factor structure and a confirmatory sample of 748 teachers (50.50% female) to test validity.ResultsThe results from the EFA indicate that the TSI-A scale is aligned well with the theoretical model, demonstrating strong internal consistency across all factors. All 49 items of the TSI-A exhibited excellent reliability, as indicated by McDonald’s omega (0.912), Cronbach’s alpha (0.923), and Gutmann’s lambda-6 (0.954) coefficients, and solid temporal stability (ICC = 0.90, 95% CI = 0.83–0.94) over 2 weeks. Similarly, the CFA fit indices were satisfactory.ConclusionThis study’s results confirmed the TSI-A’s validity for Tunisian teachers, illustrating its robust reliability and psychometric soundness. The tool is essential for identifying stressors in Tunisia’s educational environment, marked by issues such as overcrowded classrooms and resource constraints. The TSI-A can assist school administrators and policymakers in executing targeted actions to mitigate teacher stress. It establishes a foundation for cross-cultural comparisons among Arabic-speaking countries, enhancing comprehension of educator well-being in the Arab world.